Implementasi Sensor Tekanan untuk Sistem Deteksi Kebocoran pada Jaringan Pipa Distribusi Air - Kurnianingtyas, Rahajeng (JTERA (Jurnal Teknologi Rekayasa), 2025)
Leaks in water distribution networks are a major problem that causes increased water loss and decreased efficiency of clean water supply systems. This study aims to design and implement a pressure sensor-based pipe leak detection system integrated with the Internet of Things (IoT). The system uses two pressure sensors installed before and after the leak point. The ESP32 microcontroller is used for data processing and real-time data communication. Sensor calibration is carried out to ensure the accuracy of the measuring instrument through sensor testing before installation in the plant. The results of the leak test show that the system is able to detect pressure differences well at leak conditions of 30%, 50%, and 70%. The greater the leak level tested, the more significant the pressure difference between the two sensors. This system is capable of real-time pressure monitoring and offers potential applications in small and medium-sized plants. This research can be the basis for the development of an adaptive and efficient leak detection system to support sustainable water management.